Detection of high-speed railway subsidence and geometry irregularity using terrestrial laser scanning - Liu, Chun; Li, Nan; Wu, Hangbin; Meng, Xiaolin (American Society of Civil Engineers, 2014)
Subsidence and geometry deformation monitoring are essential for safe transportation on a high-speed railway. Terrestrial laser scanning (TLS) is able to collect dense three-dimensional point data from the survey scene and achieve highly accurate measurements; therefore, it is considered to be one of the most promising surveying techniques for railway track geometry deformation monitoring. This paper proposes a new approach that uses TLS to detect subsidence and irregularities in a track by fitting boundaries of the cross section of the track. In addition, for a section of local railway, an outdoor experiment was performed to ascertain the feasibility and accuracy of this method. The deformations detected with TLS were compared with the field measurements gathered with other methods such as those from a track inspection car. The results indicate that the subsidence difference between TLS and precise leveling is 2–3 mm, and the difference in the geometric parameters of the tracks is 1–2 mm. Finally, the possible causes of error involved with TLS are discussed.